Clinical outcome of platelet rich plasma versus steroid in treatment of frozen shoulder - Juneja, Johney; Jain, Mahendra Prakash; Choubisa, Raghvendra; Mehra, A. K.; Sen, Ramesh (International Journal of Research in Orthopaedics, 2021)
Background: Evaluate functional outcome of use of platelet rich plasma versus steroid in frozen shoulder. Methods: The study was conducted in Department of Orthopaedics in RNT Medical College, Udaipur. Adult patients with periarthritis shoulder (frozen shoulder or adhesive capsulitis) admitted to Trauma centre in Maharana Bhupal Government hospital attached with R.N.T. Medical College, Udaipur were included in this study after obtaining their informed, valid written consent. This is a prospective study from October 2018 to February 2020. Results: Our study demonstrated that PRP is not inferior to CS in any of the measured parameters. Both of the groups experienced similar benefits from the injection therapies with no statistical differences detected in ROM or VAS scores at 1 week, 1 month and 3 months. No adverse effects were detected in either of the two groups. Conclusions: We can conclude that both PRP and MPS showed efficacy on treating frozen shoulder. The current study provides strong evidence in support of a statistically significant effect of platelet concentrates in the treatment of frozen shoulder in vivo where steroid contraindicated or refused by patient. However, inj. Methylprednisolone has sudden onset of action because of anti-inflammatory action with respect to inj. PRP, so has better result at 1 week follow up post injection. But in long term (at 3 months follow up) inj. PRP has better effect in compared to Inj. MPS.